Tetanus epidemiology in Santa Catarina, Brazil from 1998 to 2008 Epidemiología del tétanos en Santa Catarina, Brasil, entre 1998 y 2008 - Ana Carolina S de Mattos; Clineu Gaspar H. Júnior; Alexandre M Fuentefria (Asociación Colombiana de Infectología, 2010)
Objetive: This work describes demographic and clinical characteristics of individuals with accidental tetanus in Santa Catarina, Brazil. Materials and Methods: 291 cases of accidental tetanus reported from 1998 to 2008 were analyzed retrospectively through a cross-sectional, descriptive and correlated study based on percentage and numeric frequency as well as on number and incidence rate (i.r.) found in compulsory notification forms. Results: Most cases (73,54%) occurred among men residing in Vale do Itajaí (30,24%). The age group with the highest incidence was within the 35 to 49 range (32,30%). Complete immunization history was reported in seven cases (2,40%), the perforating injury being the most observed and the lower limbs the most affected ones.Among the reported cases, 87,62% were confirmed; 114 (39,17%) patients died. Conclusions: Accidental tetanus in Santa Catarina affects the population in a significant way despite the fact that it is an immune preventable disease. The authorities and administrators must plan strategies to address changes in public policies related to immunization coverage of the susceptible population, mainly adults. Above all, it is important to warn society that the success of immunization programs depends on the application of three doses at set intervals, application of booster doses and compliance with the vaccination schedule. Objetivo: El presente trabajo describe las características demográficas y clínicas de los individuos con tétanos accidental en Santa Catarina, Brasil. Materiales y métodos: se analizaron 291 casos de tétanos accidental reportados desde el año 1998 hasta 2008, a través de un estudio descriptivo tipo corte transversal. Con base en el porcentaje y frecuencia numérica, así como en la tasa de incidencia registrada según los formularios de notificación obligatoria. Resultados: La mayoría de los casos (73,54%) ocurrieron en los hombres que residen en Vale do Itajaí (30,24%). El grupo con mayor incidencia fue en el rango de edad de 35 a 49 años (32,30%). La historia completa de inmunización se informó en siete casos (2,40%), la lesión perforante fue la más observada, las extremidades inferiores fueron las más afectadas. Entre los casos reportados 87(62%) fueron confirmados; 114 (39,17%) pacientes murieron. Conclusiones: el tétanos accidental en Santa Catarina afecta a la población de manera significativa a pesar del hecho de que es una enfermedad prevenible. Las autoridades y los administradores deben planear estrategias para generar cambios en las políticas públicas relacionadas con la cobertura de inmunización de la población susceptible, sobre todo los adultos. Es importante advertir a la sociedad que el éxito de los programas de inmunización depende de la aplicación de tres dosis a intervalos establecidos, la aplicación de las dosis de refuerzo y el cumplimiento del calendario de vacunación.